Friction stir welding of hybrid AA 6061-ZrO2-C composites FSW process optimization using desirability approach. (22nd March 2019) - Pandiyarajan, R; Maran, P; Murugan, N; Marimuthu, S; Sornakumar, T
Abstract: In the present work, friction stir welding (FSW) was employed to fabricate components made of metal matrix composites (MMC) by incorporating aluminium alloy, Zirconium Di-oxide (ZrO2 ) and Graphite (C) reinforcement particles into the aluminium AA6061 matrix. The weight percentage of MMC composition is 92% AA6061, 6% ZrO2, and 2% C. The stir cast MMC specimens were welded at the different FSW condition by changing the process parameters tool rotational speed, welding speed, and axial load. The desirability approach was used to optimize the FSW process parameters for simultaneous improvement of tensile strength and hardness of welded composites. From the investigation, it was found that the 190 MPa tensile strength and 50 HRB hardness with respective welding process parameters 852.82 rpm tool rotational speed, 48.3 mm min −1 welding speed and 5.11 kN axial load.